Third generation sequencing: technology and its potential impact on evolutionary biodiversity research. Issue 1 (2nd January 2016) - Bleidorn, Christoph
Abstract : Next generation sequencing transformed the field of evolutionary biology and high throughput sequencing platforms are routinely used in phylogenomic, population genomic or metagenomic studies. Here I review the recent technical advancements of third generation sequencing instruments, thereby covering nanopore sequencing and single molecule real-time (SMRT) sequencing. The output and error rates are compared with sequencing platforms of the second generation (454 pyrosequencing, Illumina and Ion Torrent). Third generation sequencers produce sequence reads in hitherto unprecedented lengths and will help to strongly increase the quality of genome assemblies. Moreover, the speed of sequencing and ease of sample preparation enables sequencing in the field. Even though the output and error rate of the new generation of sequencer remains to be improved, new possibilities for evolutionary research will open up in the near future by these new techniques.